Stereoselective Pd-Catalyzed Remote Hydroamination of Skipped Dienes with Azoles - Miao, Han-Zhe; Liu, Yang; Chen, Ye-Wei; Lu, Han-Yu; Li, Jian; Lin, Guo-Qiang; He, Zhi-Tao (Synlett, 2022)
A novel palladium-catalyzed stereoselective remote hydroamination reaction is disclosed. A series of azoles and skipped dienes undergo the migratory allylic C–H amination in good yields and selectivities. A desymmetric migratory azolation process is also developed to highlight the reliability of the transformation. Preliminary mechanistic experiments corroborate the designed metal walking and allylic substitution cascade strategy via Pd–H catalysis, different from prior ligand-to-ligand hydrogen transfer pathway for conjugated dienes.
Keywords: skipped diene; remote hydroamination; palladium hydride; azoles; migratory allylic C–H functionalization